Neglected Transportation Infrastructure: Corporate Social Responsibility and the Russian State in a Small Siberian Oil Town - Gertrude Saxinger (Department of Political Science, Faculty of Social Sciences, University of Vienna); Natalia Krasnoshtanova (V.B. Sochava Institute of Geography, Russian Academy of Sciences); Gertraud Illmeier (Department of Social and Cultural Anthropology, Faculty of Social Sciences, University of Vienna) (Sibirica, 2021)
The abstract is available here: https://uscholar.univie.ac.at/o:1596499 The abstract is available here: https://uscholar.univie.ac.at/o:1596499